Aberrant attentional bias to sad faces in depression and the role of stressful life events: Evidence from an eye-tracking paradigm. (December 2020) - Klawohn, Julia; Bruchnak, Alec; Burani, Kreshnik; Meyer, Alexandria; Lazarov, Amit; Bar-Haim, Yair; Hajcak, Greg
Abstract: Attentional biases are thought to be involved in the etiopathogenesis of depressive disorders. Recent studies indicate eye-tracking techniques could overcome methodological issues of traditional reaction time bias measures and be used to reliably quantify biases in attention. In the current study, 50 participants with a current depressive disorder and 31 never-depressed individuals performed a free-viewing eye-tracking paradigm with two counterbalanced blocks; one contained four-by-four arrays of happy and neutral faces, the other arrays of sad and neutral faces. Average dwell-times were analyzed, and internal consistency was examined. Dwell-time measures had good to excellent internal consistency. Both groups were characterized by increased dwell-time to happy compared to neutral faces (i.e., bias toward positive faces). Never-depressed participants showed a bias away from sad stimuli (i.e., increased dwell-time to neutral compared to sad faces), that was not evident in the depressed group. Moreover, depressed individuals dwelled longer on sad stimuli than never-depressed participants. Within depressed participants, bias to sad faces was associated with both childhood trauma and recent negative life events. Results demonstrate that an attentional bias towards sad faces in depression can be reliably assessed using free-viewing eye-tracking technique and its magnitude is exacerbated by the experience of stressful life events. Highlights: Attentional biases in 50 currently depressed and 30 never depressed participants. Blocked free-viewing eye-tracking paradigm using complex face stimuli grids. Bias towards happy compared to neutral faces present in both groups. Increased dwell time to sad faces and reduced bias away from sad in depression. Sad bias in depression associated with childhood trauma and negative life events.